Strategi Kolaboratif Mewujudkan Ruang Terbuka Hijau (RTH) - Yulianti, Wiwik; Hadi, Sudharto P. (Universitas Sebelas Maret, 2017)
Fulfilling the need of housing is essential for the community. The growth of housing in urban area decreases the environmental carrying capacity. To restore the carrying capacity of the urban area and to harmonize the growth of the built area with the natural environment, the government issued the Act No. 26 of 2007 on Spatial Planning in which Green Open Space must reach 30% of the total urban area, consisting of 20% public and 10% private green open space. Fulfilling the proportion of public green open space is still difficult to be realized. As a case study, the public green open space is 88,145,5 m2 or 0,036% of total urban area in Kendal Regency. In order to increase the green open space in urban area, the building permit mechanism in Kendal Regency requires the siteplan document as one of the technical requirements in the Standard Operating Procedure (SOP), the minimum requirement of private green open space to be fulfilled by 10% of the total housing area. Thus, it is expected that the growth of green open space follows the growth of housing in Kendal Regency. Through collaborative governance among stakeholders involved in Kendal Regency Licensing Team in the implementation of building permit regulation, private green open space at housing estates area is expected to be fulfilled. This study reviews the maturity level of the building permit regulation implementation by reviewing organizational, actors, management, and external (surroundings) characteristics. Analytical Hierarchy Process (AHP) and scoring method is used in the process of formulating the priority of indicators, criteria, variables, and assessment of maturity level of the building permit regulation implementation on the fulfillment of green open space in the housing estates in Kendal Regency. Based on the assessment result, the proposed implementation strategy can be formulated.